2013
DOI: 10.1073/pnas.1219002110
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of cellular polyamines, spermidine and spermine, causes a total arrest in translation and growth in mammalian cells

Abstract: The polyamines, putrescine, spermidine, and spermine, are essential polycations, intimately involved in the regulation of cellular proliferation. Although polyamines exert dynamic effects on the conformation of nucleic acids and macromolecular synthesis in vitro, their specific functions in vivo are poorly understood. We investigated the cellular function of polyamines by overexpression of a key catabolic enzyme, spermidine/spermine N 1 -acetyltransferase 1 (SAT1) in mammalian cells. Transient cotransfection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
198
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(210 citation statements)
references
References 41 publications
(47 reference statements)
8
198
2
2
Order By: Relevance
“…Although other groups using transient transfection (27,43) previously reported that SAT1 overexpression causes rapid cell-growth arrest in HeLa cells and apoptosis in glioblastoma cells, we observed neither of these phenomena in our inducible expression system. These differing results may be attributable to the levels of SAT1 being expressed in cells, because the lower level of SAT1 expression induced by tetracycline may mimic the physiological condition better than transient transfection.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Although other groups using transient transfection (27,43) previously reported that SAT1 overexpression causes rapid cell-growth arrest in HeLa cells and apoptosis in glioblastoma cells, we observed neither of these phenomena in our inducible expression system. These differing results may be attributable to the levels of SAT1 being expressed in cells, because the lower level of SAT1 expression induced by tetracycline may mimic the physiological condition better than transient transfection.…”
Section: Discussioncontrasting
confidence: 85%
“…1A, SAT1 catalyzes the acetylation of spermidine and spermine to form N 1 -acetylspermidine and N 1 -acetylspermine, which then are either exported from the cells or converted back to putrescine or spermidine by N 1 -acetylpolyamine oxidase (26). Therefore, overexpression of SAT1 leads to an overall depletion of spermidine and spermine while increasing the levels of putrescine, N 1 -acetylspermidine, and N 1 -acetylspermine (27). In fact, N 1 , N 11 -di(ethyl)norspermine (DENSpm), a polyamine analog that is known to induce SAT1, has been applied in several clinical trials in patients with advanced malignancies (28)(29)(30)(31).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Involvement of PAs in plant responses to environmental stimuli has been demonstrated by several studies. The protective effects of elevated endogenous level (either due to exogenous PA treatment or to transgenic modification) have been reported in several plant species under various stress conditions [1][2][3][4][5][6][7][8][9][10][11]. Besides their direct protective role PAs regulate fundamental cellular processes as signalling molecules, suggesting that abiotic stress tolerance is mainly influenced via signalling processes rather than by their accumulation [12].…”
Section: Introductionmentioning
confidence: 99%
“…The literature has reported a link between spermine and growth. Depletion of spermine and spermidine led to an entire arrest in translation and growth in HEK293 cells, and a direct role for polyamines in the initiation of translation was suggested 240 . Other scientists observed that polyamines were needed at the initiation and at the elongation steps of translation: they showed that spermine is a precursor in the hypusination of the eukaryotic initiation factor 5A (eIF5A) that acts as a translation elongation factor 241 .…”
Section: Discussionmentioning
confidence: 99%